Comparison On Success Factors Over The Malaysian And Mauritian Constructions Projects - Yashweenee, Bundhun (2018)
Construction projects play an important role in the advancement of a nation through Infrastructure development that leads to economic growth. Nowadays, delivering successful construction project are therefore becoming much more challenging for every project manager. Not all the projects achieved the goals as per planned. Consequently, the study of project success and critical success factors are considered as one of the potential means for achieving project success. The objective of this study is to identify those success factors and critical success factors and focus is on Malaysia and Mauritius. A comparison between the identified critical success factors of the Malaysian construction projects to the Mauritian one was done. Using questionnaire with significant score and relative important index to identify critical success factors, the survey found ten CSFs for the Mauritian construction projects which are firstly, good communication followed by emphasis on cost, quality and time, adequacy of funding, availability of resources (workers & machines), well prepared tendering documents, client satisfaction,identification of project of project difficulties, Project Manager’s experience & competence, site Investigation effectiveness and lastly safety on site. While for Malaysian, the ten CSFs are client Satisfaction, client’s needs & specifications, project Manager’s experience & competence, quality control effectiveness, availability of resources, commitment of stakeholder’s, safety on site, adequacy of funding, trust-based relationship with client, budget updates. It is recommended to focus more on the identification of project difficulties for the Mauritian construction projects while for Malaysia, implementation of effective construction quality control process is necessary for delivering high quality construction products.